A Robust Scheduling Methodology for Integrated Electric-Gas System Considering Dynamics of Natural Gas Pipeline and Blending Hydrogen - Yan, Daobo; Wang, Shu; Zhao, Hongsheng; Zuo, Lianyong; Yang, Dongjun; Wang, Shengshi; Yan, Jiong (Frontiers in Energy Research, 2022)
As smart grid develops and renewables advance, challenges caused by uncertainties of renewables have been seriously threatening the energy system’s safe operation. Nowadays, the integrated electric-gas system (IEGS) plays a significant role in promoting the flexibility of modern grid owing to its great characteristic in accommodating renewable energy and coping with fluctuation and uncertainty of the system. And hydrogen, as an emerging and clean energy carrier, can further enhance the energy coupling of the IEGS and promote carbon neutralization with the development of power-to-hydrogen (P2H) technology and technology of blending hydrogen in the natural gas system. Dealing with the uncertainty of renewables, a robust schedule optimization model for the integrated electric and gas systems with blending hydrogen (IEGSH) considering the dynamics of gas is proposed and the iterative solving method based on column-and-constraint generation (C&CG) algorithm is implemented to solve the problem. Case studies on the IEGSH consisting of IEEE 39-bus power system and 27-node natural gas system validate the effectiveness of the dynamic energy flow model in depicting the transient process of gas transmission. The effectiveness of the proposed robust day-ahead scheduling model in dealing with the intra-day uncertainty of wind power is also verified. Additionally, the carbon emission reduction resulting from the blending of hydrogen is evaluated.